1991
DOI: 10.1037/0278-6133.10.3.173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reviewing risk-relevant behavior on perceived vulnerability among women marines.

Abstract: People generally underestimate their own vulnerability to negative events such as illness or accidents. It has been suggested that this illusion of "unique invulnerability" is due to selective focus on one's own risk-reducing behaviors, to the exclusion of others' risk-reducing behaviors and one's own risk-increasing behaviors. The current study examined the effects of reviewing sexual and contraceptive behavior on perceived vulnerability to unplanned pregnancy. Our results indicated that review of pregnancy-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 19 publications
7
64
1
Order By: Relevance
“…This finding provides experimental support for the results obtained by Gerrard et al (1991) who used a correlational methodology. Thus, although previous research has indicated that review of risk relevant factors increases optimism (Weinstein, 1983), the results of the present study suggest that it may not be review per se, but review of risk decreasing factors which leads to an increase in perceptions of invulnerability.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding provides experimental support for the results obtained by Gerrard et al (1991) who used a correlational methodology. Thus, although previous research has indicated that review of risk relevant factors increases optimism (Weinstein, 1983), the results of the present study suggest that it may not be review per se, but review of risk decreasing factors which leads to an increase in perceptions of invulnerability.…”
Section: Discussionsupporting
confidence: 81%
“…Research shows that in comparison to a no-review control group, optimism actually increases after review of risk behaviour for a variety of health problems (Weinstein, 1983). For example, Gerrard, Gibbons & Warner, (1991) examined the effects of reviewing both risk increasing behaviour (eg., frequency of sexual intercourse) and risk decreasing behaviour (eg., contraceptive use) on perceived risk to unplanned pregnancy. The results revealed that in comparison to a control group optimism increased after review of behavioural risk factors.…”
mentioning
confidence: 99%
“…The evidence indicates that individuals' inability to make accurate estimates tends to maintain an illusion of themselves as invulnerable, or they show an optimistic bias (McKenna, 1993;Weinstein, 1980). Studies of perceived vulnerability have demonstrated that people tend to think that they are less vulnerable than others to negative events (Weinstein, 1987;Gerrard, 1991).…”
Section: Perceived Vulnerabilitymentioning
confidence: 99%
“…In a similar manner, people have a better memory for behavioral guidelines that place their behavior in a favorable (healthy) light than for those that place it in an unfavorable (unhealthy) light (66). Finally, when asked to consider their own behavioral prac tices, people may selectively focus on the preventive actions that they have adopted rather than on the risks that they have taken [ (53,67); for a complete discussion of these fi ndings, see Gerrard et al, this monograph].…”
Section: Recognizing the Limitations Of A Contextually Based Communicmentioning
confidence: 99%
“…Interventions that heighten the salience of factors that place people at risk for adverse outcomes have typically involved directing their attention to relevant aspects of their behavior or personal attributes. For instance, Gerrard et al (53) had female Marines review their sexual and contraceptive his tories prior to assessing their risks for pregnancy and human immunodefi ciency virus (HIV) infection. Th is behavioral review heightened judgments of personal risk for HIV infection and, in some cases, personal risk for pregnancy.…”
Section: Impact Of Contextualized Approachesmentioning
confidence: 99%